IDEOLOGY, VALUES AND NORMS IN HIP-HOP COMMUNITY WIJILAN YOGYAKARTA: AN ETHNOGRAPHIC STUDY - Dahlan, A. Fahmi; Adi, Ida Rochani (Pengkajian Amerika, Universitas Gadjah Mada, 2025)
This research explores the cultural adaptation of American hip-hop in Wijilan, Yogyakarta, focusing on the dynamics of hybridity between global and local cultures. Hip-hop, originally rooted in the Bronx during the 1970s, has become a global cultural force that merges with various traditions worldwide. In Wijilan, the hip-hop community has blended the individualistic values of American hip-hop with the Javanese collective ethos of gotong royong. This fusion results in unique artistic expressions. Using ethnographic methods, this study reveals hip-hop's role as an ideology through identity formation, resistance, cultural expression, and social commentary within communities by observing practices, exploring identity, highlighting resistance, interpreting symbols, and assessing impact. Events, like Soringin Hip-hop Festival, highlight the role of hip-hop as a platform for cultural exchange and social commentary, showcasing a blend of music, graffiti, and dance that embodies both local and global influences. The study concludes that the cultural hybridity in Wijilan’s hip-hop community fosters a new, dynamic identity that maintains traditional values while embracing contemporary, global trends, contributing to both cultural preservation and innovation.